A forum on minds and institutions. Issue 3 (28th April 2015) - FELIN, TEPPO
Abstract: The purpose of this special topic forum is to call for research on the topic of minds and institutions. I briefly discuss three specific research opportunities: (1) bounded rationality versus mind, (2) many minds and the interfaces of institutions, (3) the affordances of institutions and arbitrage. I then briefly introduce the two special topic forum papers and highlight how they link to the topic of minds and institutions.